2011
DOI: 10.1007/s10571-011-9716-z
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Botulism Triterpenoid Toosendanin Elicits Calcium Increase and Exocytosis in Rat Sensory Neurons

Abstract: Toosendanin, a triterpenoid from Melia toosendan Sieb et Zucc, has been found before to be an effective anti-botulism agent, with a bi-phasic effect at both motor nerve endings and central synapse: an initial facilitation followed by prolonged depression. Initial facilitation may be due to activation of voltage-dependent calcium channels plus inhibition of potassium channels, but the depression is not fully understood. Toosendanin has no effect on intracellular calcium or secretion in the non-excitable pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The minimum effective histone concentration was found to be 2 mgL −1 (b); higher concentrations (5, 20 mgL −1 ) (c,d) induced progressively stronger calcium oscillations (Figure 3A–E). Note the varied resting F 340 /F 380 ratio levels among different cells, which have also been noted before, and are normalized when performing data analysis [46,47,49]. Integrated calcium responses were plotted against histone concentrations for each histone (H1, H2A, H2B, H3, and H4) and are presented in both bar charts and line curves (Figure 3Fa,Fb).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum effective histone concentration was found to be 2 mgL −1 (b); higher concentrations (5, 20 mgL −1 ) (c,d) induced progressively stronger calcium oscillations (Figure 3A–E). Note the varied resting F 340 /F 380 ratio levels among different cells, which have also been noted before, and are normalized when performing data analysis [46,47,49]. Integrated calcium responses were plotted against histone concentrations for each histone (H1, H2A, H2B, H3, and H4) and are presented in both bar charts and line curves (Figure 3Fa,Fb).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent calcium imaging was done as reported previously [6,44,47,48] in a Photon Technology International (PTI, Ediosn, N.J., USA) calcium measurement system, with a photon-counting PMT (PTI PMT814) or a CCD (NEO-5.5-CL-3, Andor) as detector, in an inverted fluorescent microscope (Olympus IX or Nikon NE 300), with fluorescence collected at 510 ± 25 nm. The fluorescent ratios of F 340 /F 380 were shown as indications of calcium concentrations and were plotted against time with SigmaPlot as before [6,47,49].…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic calcium was measured in an inverted fluorescent microscope (Nikon TE-2000U) coupled to a PTI (Photon Technology International Inc., now HORIBA, Edison, NJ, USA) calcium measurement system with alternating excitations of the loaded Fura-2 at 340 nm/380 nm (DeltaRam X), and emitted Fura-2 fluorescence (dichroic mirror 400DCLP, emitter 510 ± 40 nm) was detected with a charge-coupled device (CCD) camera (NEO-5.5-CL-3, Andor/Oxford Instruments, UK). Calcium concentration was expressed as F 340 /F 380 ratios and plotted against time with SigmaPlot, as reported before [1,2,28,31,33,52,53]. In the figures shown in Results, the original colored calcium tracings were each from individual cells and only representative tracings from 1 out of N (as indicated, N ≥ 3) identical experiments were presented.…”
Section: Calcium Measurementsmentioning
confidence: 99%
“…Toosendanin (TSN) is a triterpenoid saponin isolated from the Chinese herb Melia toosendan and is known to inhibit acetylcholine release at the nerve terminals. Though used as a pesticide, recent studies have shown its anti-proliferative effect against lymphoma, leukemia and hepatocellular cancer cell lines [ 225 228 ]. In addition, TSN also inhibits proliferation of U87 and C6 cell line at nanomolar (10 nM) concentrations [ 229 ].…”
Section: Effects Of Natural Products On Gbm Pre-clinical Modelsmentioning
confidence: 99%